2021
DOI: 10.1159/000516880
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Radiation Therapy of Unresectable Intrahepatic Cholangiocarinoma: Internal or External? A Systematic Review and Meta-Analysis

Abstract: <b><i>Purpose:</i></b> Both external beam radiation therapy (EBRT) and selective-internal radiation therapy (SIRT) are implemented to treat unresectable intrahepatic cholangiocarcinoma (iCCA). The present study aimed to evaluate the efficacy of EBRT and SIRT in managing iCCA through a systematic review and meta-analysis. <b><i>Methods:</i></b> PubMed and Cochrane database were queried to search for studies published from January 2000 toJune 2020 without language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
2
2
0
Order By: Relevance
“…On the basis of the present study, the pooled TRR and TCR were 36%–49% and 73%–97%, respectively. These findings are similar to previously reported 22%–81% and 78%–96% in the primary liver cancer such as cholangiocarcinoma ( 48 ). Radiological response is a well-known predictor of survival after SIRT of HCC and colorectal liver metastasis ( 49 , 50 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the basis of the present study, the pooled TRR and TCR were 36%–49% and 73%–97%, respectively. These findings are similar to previously reported 22%–81% and 78%–96% in the primary liver cancer such as cholangiocarcinoma ( 48 ). Radiological response is a well-known predictor of survival after SIRT of HCC and colorectal liver metastasis ( 49 , 50 ).…”
Section: Discussionsupporting
confidence: 92%
“…(46,47). While the comparative studies between EBRT and SIRT were lacking in the setting of breast cancer metastasis to the liver, a previous study on cholangiocarcinoma showed a seemingly longer survival of SIRT over EBRT as the first-line therapy (MST of 36 vs. 11 months) (48), highlighting SIRT's effectiveness in reducing hepatic tumor burden as a novel therapy compared with the more traditional EBRT approach. On the basis of the present study, the pooled TRR and TCR were 36%-49% and 73%-97%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time was 13.6 months and 12 months for EBRT and SIRT, respectively. When comparing treatments, it was found that current studies are too heterogeneous for there to be definitive conclusions [19]. Similar findings were found by Edeline et al, who completed a pooled analysis of various locoregional therapies, including EBRT and SIRT.…”
Section: Unresectable or Inoperable Ccasupporting
confidence: 78%
“…In addition to these studies examining radiotherapy, several studies on trans-arterial chemoembolization (TACE), hepatic arterial infusion (HAI), TARE, and radiofrequency ablation (RFA) have shown mixed findings in the treatment of unresectable intrahepatic ICC and remain active areas of investigation [3]. Retrospective comparisons between RT and other modalities have been inconclusive given the wide heterogeneity of patients treated across modalities [25].…”
Section: Hypofractionated Rt For Iccmentioning
confidence: 99%